6.8k views
1 vote
I already know the answer to this problem, I want a explanation on how to get the answer.

I already know the answer to this problem, I want a explanation on how to get the-example-1
User GuyRT
by
5.0k points

2 Answers

0 votes


\\ \bull\tt\dashrightarrow BC=CE


\\ \bull\tt\dashrightarrow 3x+3y=7x+5y


\\ \bull\tt\dashrightarrow 7x-3x=3y-5y


\\ \bull\tt\dashrightarrow 4x=-2y


\\ \bull\tt\dashrightarrow 2x=-y


\\ \bull\tt\dashrightarrow (x)/(y)=(-1)/(2)

Now


\\ \bull\tt\dashrightarrow BE=BC+CE+CD


\\ \bull\tt\dashrightarrow BE=3x+3y+7x+5y+5x-2y+6


\\ \bull\tt\dashrightarrow BE=15x+6y+6

User Wiggy
by
4.6k points
1 vote

Answer:

• BC = CD


(3x + 3y) = (5x - 2y + 6) \\ 5x - 3x = - 2y - 3y + 6 \\ 2x = - 5y + 6 \\ \\ \dashrightarrow \: { \tt{x = ( - 5y + 6)/(2) }}

• find BE:


\dashrightarrow \: { \tt{BE = (3x + 3y) + (7x + 5y)}} \\ \\{ \tt{BE = 10x + 8y}}

User Maselko
by
5.0k points